Analisis Komparatif Kinerja Keuangan Bank Umum Syariah di Indonesia Dan Bank Umum Syariah di Malaysia dengan Pendekatan Islamicity Performance Index - Ayu, Dewi; Hermawan, Dadang; Nurdin, Ade Ali; Juniwati, Endang Hatma (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
This study aims to analyze the differences in the financial performance of Islamic banks in Indonesia and Malaysia with the Islamicity Performance Index (IPI). The data collection method used is the Annual Report published on the official website of each bank. The research sample used was 14 banks, consisting of 7 Islamic banks in Indonesia and 7 Islamic banks in Malaysia. The results of testing using the Mann-Whitney U Test stated that there was no significant difference between Islamic Banks in Indonesia and Malaysia for ZPR and IIR. Although the graph shows that the distribution of zakat in Malaysian Islamic banks is higher than in Indonesia. PSR stated that there are significant differences between Islamic banks in Indonesia and in Malaysia. For the graph, Indonesia is higher than Malaysia because the products of Islamic banks in Malaysia are more diverse and products based on profit-loss sharing are almost non-existent.